Réponses

Meilleure réponse !
2014-05-10T15:34:34+02:00
2x (3x+2)(3x - 1) = 0
<=> 2x = 0 OU 3x+2 = 0 OU 3x-1 = 0
<=> x = 0
OU 3x = -2 OU 3x = 1
<=> x = 0 
OU x = -2/3 OU x = 1/3

S={0; -2/3; 1/3}

(3x - 1) + (7 - x) = 0
<=> 2x + 6 = 0
<=> 2x = -6
<=> x = -3

S={-3}

(8 + 3x) - (x + 3) = 0
<=> 8 + 3x - x - 3 = 0
<=> 2x + 5 = 0
<=> 2x = -5
<=> x = -5/2

S={-5/2}

6(y + 3) - 2(y - 1) = 0
<=> 6y + 18 - 2y + 2 = 0
<=> 4y = 20
<=> y = 20/4
<=> y = 5

S={5}








merci beaucoup lechtidu56
Y'a pas de soucis si je peux aider! N'hésite pas à passer ma réponse comme "Meilleure réponse"!